CLIMATE AND WILDFIRE IN THE WESTERN UNITED STATES - Westerling, A. L.; Gershunov, A.; Brown, T. J.; Cayan, D. R.; Dettinger, M. D. (Bulletin of the American Meteorological Society, 2003)
A 21-yr gridded monthly fire-starts and acres-burned dataset from U.S. Forest Service, Bureau of Land Management, National Park Service, and Bureau of Indian Affairs fire reports recreates the seasonality and interannual variability of wildfire in the western United States. Despite pervasive human influence in western fire regimes, it is striking how strongly these data reveal a fire season responding to variations in climate. Correlating anomalous wildfire frequency and extent with the Palmer Drought Severity Index illustrates the importance of prior and accumulated precipitation anomalies for future wildfire season severity. This link to antecedent seasons' moisture conditions varies widely with differences in predominant fuel type. Furthermore, these data demonstrate that the relationship between wildfire season severity and observed moisture anomalies from antecedent seasons is strong enough to forecast fire season severity at lead times of one season to a year in advance.